Energy and protein requirements of crossbred (Holstein × Gyr) growing bulls - Oss, D. B.; Castro, M. M. D.; Silva, T. E. da; Marcondes, M. I.; Machado, F. S.; Tomich, T. R.; Pereira, L. G. R.; Campos, M. M. (Journal of Dairy Science, 2017)
The objective of this study was to estimate the energy and protein requirements of crossbred (Holstein × Gyr) growing bulls. Twenty-four 10-mo-old bulls [initial body weight (BW) = 184 ± 23.4 kg] were used in a comparative slaughter trial. Six bulls were slaughtered at the beginning of the experiment as the reference group, to estimate initial empty body weight (EBW) and energy and protein contents of the remaining animals. The remaining bulls were assigned to a completely randomized design with 3 levels of dry matter intake and 6 replicates. The levels of dry matter intake were 1.2% of BW, 1.8% of BW, and ad libitum to target orts equal to 5% of the total amount that was fed. The remaining bulls were slaughtered at the end of the experiment. The bulls were fed a diet consisting of 59.6% corn silage and 40.4% concentrate on a dry matter basis. The equation that determined the relationship between EBW and BW was EBW = (0.861 ± 0.0031) × BW. The relationship between empty body gain (EBG) and average daily gain (ADG) was demonstrated by the following equation: EBG = (0.934 ± 0.0111) × ADG. Net energy for maintenance (NEM) was 74.8 ± 2.89 kcal/kg of EBW0.75 per day, and metabolizable energy for maintenance (MEM) was 120.8 kcal/kg of EBW0.75 per day. The detected efficiency of use of metabolizable energy for maintenance (km) was 61.9%. The equation used to estimate net energy for gain (NEG) was as follows: NEG = (0.049 ± 0.0011) × EBW0.75 × EBG0.729 ± 0.0532. The efficiency of use of metabolizable energy for gain (kg) was 35.7%. The metabolizable protein for maintenance (MPM) was 3.05 g/kg of BW0.75. The equation used to estimate net protein requirements for gain (NPG) = (87.138 ± 65.1378 × EBG) + [(40.436 ± 21.3640) × NEG]. The efficiency of use of metabolizable protein for gain (k) was 35.7%. We concluded that the estimates of energy and protein requirements presented herein are more appropriate than the National Research Council dairy cattle model and the Brazilian BR-CORTE system to balance the diets of crossbred (Holstein × Gyr) growing bulls
Keywords: Bos indicus; Growth; Gyr; Holstein; Maintenance